Handbook of engineering acoustics - Muller, Gerhard; Moser, Michael (Springer, 2013)
This acoustics handbook for mechanical and architectural applications is a translation of the German standard work on the subject. It not only describes the state of art of engineering acoustics but also gives practical help to engineers for solving acoustic problems. It deals with the origin, the transmission and the methods of abatement of air-borne and structure-borne sound of different kinds, from traffic to machinery and flow induced sound.